2011
DOI: 10.1007/s10479-011-0867-6
|View full text |Cite
|
Sign up to set email alerts
|

Managing the tabu list length using a fuzzy inference system: an application to examination timetabling

Abstract: In this paper, we present an application of Tabu Search (TS) to the examination timetabling problem. One of the drawbacks of this meta-heuristic is related to the need of tuning some parameter (like tabu tenure) whose value affects the performance of the algorithm. The importance of developing an automatic procedure is clear considering that most of the users of timetabling software, like academic staff, do not have the expertise to conduct such tuning. The goal of this paper is to present a method to automati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Pais and Amaral [22] implemented an improved tabu search for the examination timetabling. Here, tabu list is automatically tuned by a fuzzy inference rule-based system (FIRBS), and this improves tabu search in exploring a promising area of solution space.…”
Section: Related Workmentioning
confidence: 99%
“…Pais and Amaral [22] implemented an improved tabu search for the examination timetabling. Here, tabu list is automatically tuned by a fuzzy inference rule-based system (FIRBS), and this improves tabu search in exploring a promising area of solution space.…”
Section: Related Workmentioning
confidence: 99%
“…Conventionally, fixed length tabu lists are usually implemented, but in [10], it was shown that fixed length list cannot always prevent cycling as such variable length list may also be considered. In [16], a fuzzy inference rule based system (FIRBS), based on frequency and inactivity, was developed and used to manage the tabu list length for examination timetabling, resulting in improved performance.…”
Section: Tabu Search (Ts)mentioning
confidence: 99%
“…One last question to be solved in order to have specified all the elements of the model (8) is to determine the b j , i.e., the proportion allocated to each mental account. To do so, we propose to use fuzzy inference systems (Mamdani and Assilian 1975;Takagi and Sugeno 1985;Jang 1993;Pais and Amaral 2012).…”
Section: Determining the Aspiration Levels For The Financial Objectivmentioning
confidence: 99%